Culturally Responsive Teaching and Critical Thinking in Elementary Social Studies: A Quasi-Experimental Study - Intan Nuraini; Eka Yusnaldi (Yayasan Sembilan Pemuda Indonesia, 2026)
This research aims to examine how the implementation of Culturally Responsive Teaching affects the critical thinking skills of fourth-grade students in Social Studies at SD Negeri 054915. The research design is quasi-experimental with a nonequivalent control group design. The sample consisted of 43 students from two classes, divided into two groups: the experimental class (n = 23), which was taught using the Culturally Responsive Teaching approach, and the control class (n = 20), which was taught using traditional learning methods. Information was collected through pre-tests and post-tests that had been tested for validity and reliability. The research findings indicate that this method has an impact on students’ critical thinking skills in Social Studies. Based on hypothesis analysis using an independent t-test, the significance value (sig. 2-tailed) was 0.000 < 0.05, meaning that H0 was rejected and Ha was accepted. Therefore, the Culturally Responsive Teaching approach was proven effective in improving students’ analytical thinking skills in Social Studies education at the elementary school level. The control group, which did not use the Culturally Responsive Teaching approach, had an average (mean) score of 64.20, according to the data analysis. In contrast, the students in the experimental class, who were taught using the Culturally Responsive Teaching approach, achieved an average score of 74.52. These findings indicate that the Culturally Responsive Teaching approach has a significant impact on improving students’ critical thinking skills. By linking the learning material to students’ cultural backgrounds, the learning process becomes relevant, motivating, and encourages students to analyze information more deeply. The novelty of this research lies in the specific application of the Culturally Responsive Teaching approach in the Social Studies subject, particularly in the topic of cultural diversity, to develop critical thinking skills based on Ennis’ indicators. These findings provide supporting evidence for this approach as an effective learning strategy, and it is recommended that Culturally Responsive Teaching be more widely integrated into Social Studies education, with future research involving larger samples and long-term measurements.